أثر استخدام الوسائل البصرية لمفردات اللغة العربية على قدرة حفظ المفردات لدى التلاميذ بمدرسة مفتاح الهدى الثانوية الإسلامية سنتاڠ - agustin, sumiati; Aprilyanti, Media (Institut Agama Islam Negeri Pontianak, 2023)
This study aims to: (1) Know the ability to memorize Arabic vocabulary of MTs Miftahul Huda students before using mufradat visual media (2) Know the memorization ability of MTs Miftahul Huda students after using mufradat visual media (3) Find out how much the effect of using mufradat visual media is. Arabic on the ability to memorize vocabulary of MTs Miftahul Huda students. This type of quantitative research with Posttest-Only Non Equivalent Control Group Design. The population in this study were 20 experimental class students and 20 control class students. Research instruments in the form of observation, documentation and tests. The data analysis technique used is descriptive analysis and simple linear regression analysis. The results showed that: 1) Obtaining the results of the data by the final test or posttest on students after being given the use of Arabic mufradat visual media, so that the average result of the final exam score for the experimental class students was 30.25 and the control class was 40.50 by conducting a descriptive test in SPSS 25. 2) Get the results of the data with the final test or posttest on students after being given the use of Arabic mufradat visual media, so that the average result of the final exam score for the experimental class students is 82.25 and the control class is 70.50 by conducting a descriptive test on SPSS 25.3) Knowing the value of mufradat visual media on the ability to memorize Arabic vocabulary with the results of the f-count test in a simple linear regression test with the result of f-count = 3.049, which has a significance of 0.089 <0.05, then Ho is rejected and H1 is accepted. What can be explained is that visual Arabic mufradat media has an effect on students' ability to memorize vocabulary.